Answer:
( x y -6)² = x² y² - 12 xy + 36
Step-by-step explanation:
<u><em>Explanation:-</em></u>
Given that the expression ( x y -6)²
Apply formula (a-b)² = a² -2ab + b²
( x y -6)² = (xy)² - 2 × xy× 6 + (6)²
= x² y² - 12 xy + 36
( x y -6)² = x² y² - 12 xy + 36
Answer:
1.5 because it is the average of the two middle numbers in this scenario.
Answer:
3
Step-by-step explanation:
Mean = (3+7+-1+1+0+5+-3+2+-1+6+5+-2)/12
= 1.833
median is middle of ordered numbers -3/-2/-1/-1/0/1/2/3/5/5/6/8/7 here between the 6th and the 7th since with even number sample, there is not a unique middle. This would be 1.5
Standard deviation = √ 123.67/12
√10.3
=3.21
the change score that is 2.2 standard deviations below the mean.
1.83 - 2.2(3.21)
= 5.232
Answer:
59
Step-by-step explanation: